Balinese Script as A Window to Understanding the Depth of Nusantara Literature Philosophy (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2026)
This study examines Balinese script as a symbolic system that serves as a gateway to understanding the philosophical depth of Nusantara literature. Employing a qualitative approach with a descriptive-interpretative design, this research analyzes classical Balinese texts, including lontar, kakawin, and geguritan, to explore the philosophical meanings embedded within the script. Data were collected through document analysis, observation, and in-depth interviews, and were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings reveal that Balinese script is not merely a writing system but a complex symbolic medium that embodies spiritual, ethical, and cosmological values. It functions as a bridge between the physical (sekala) and spiritual (niskala) realms, enabling deeper interpretation of literary texts beyond their literal meanings. Furthermore, the script plays a crucial role in preserving and transmitting philosophical knowledge across generations through traditional manuscripts. However, the study also identifies significant challenges in the preservation of Balinese script in the digital era, including declining literacy among younger generations, limited access to traditional manuscripts, and insufficient integration into modern digital platforms. In response, the study highlights the importance of holistic revitalization strategies, including digital innovation, culturally responsive education, community engagement, and policy support to ensure its sustainability. Theoretically, this research contributes to the development of literary and cultural studies by positioning script as a central element in meaning-making processes. Practically, it offers insights into the preservation and revitalization of local cultural heritage in the context of globalization. Ultimately, Balinese script is reaffirmed not only as a cultural artifact but also as a living knowledge system that remains relevant in contemporary society.